CYBER INTELLIGENCE PRACTICE IN PREVENTING CYBER THREATS AND ITS PRIORITIES - Ganiyev Abdukhalil; Tojimatov Dostonbek (PT ANTIS International Publisher, 2024)
The practice of cyber intelligence is a comprehensive data collection process aimed at identifying, identifying, classifying, and strategizing any threats or risks to information assets. This article aims to describe and explain the current relevance of cyber-intelligence practice in preventing cyber-threats, the methods and techniques of conducting cyber-intelligence, and the basics of technologies. The article contains suggestions for increasing the effectiveness of cyber defense and developing the systemic immune response against various cyber threats